Respuesta :

Space

Answer:

x = 4

y = -3

Step-by-step explanation:

We can use substitution, elimination, or graphically.

Step 1: Rearrange first equation

2x + 4y = -4

2x = -4 - 4y

x = -2 - 2y

Step 2: Rewrite systems of equations

x = -2 - 2y

3x + 5y = -3

Step 3: Substitution

3(-2 - 2y) + 5y = -3

-6 - 6y + 5y = -3

-6 - y = -3

-y = 3

y = -3

Step 4: Find x using y

2x + 4(-3) = -4

2x - 12 = -4

2x = 8

x = 4

Graphically:

Use a graphing calc and analyze where the 2 lines intersect.

Ver imagen Space